Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Astruch, Patrick; Orts, Ameline; Schohn, Thomas; Belloni, Bruno; Ballesteros, Enric; Bănaru, Daniela; Bianchi, Carlo Nike; Boudouresque, Charles-François; Changeux, Thomas; Chevaldonné, Pierre; Harmelin, Jean-Georges; Michez, Noëmie; et al. (Frontiers in Marine Science, 2023)
Introduction Coastal detrital bottoms (CDB) are one of the most extensive habitats of the continental shelf worldwide, in the upper levels of the circalittoral zone. Hosting a diverse community structured by sediment grain size, trophic interactions and calcified organisms, CDB exhibit important ecological functions. In the Mediterranean Sea, CDB are constituted by recent elements partly provided by adjacent infralittoral and circalittoral ecosystems. Since the 2010s, the offshore extension of many Marine Protected Areas (MPAs) has resulted in the incorporation of vast areas of CDB, raising the issue of their management. The Marine Strategy Framework Directive (MSFD) has embraced the concept of an ecosystem-based approach involving taking into account the functioning of marine habitats and their related ecosystem services. The purpose of this paper is to propose an ecosystem-based quality index (EBQI) tested on CDB from the north-western Mediterranean Sea, focusing mainly on epibenthic assemblages. Methods The first step has been to define a conceptual model of the CDB functioning, including the main trophic compartments and their relative weighting, then to identify appropriate assessment methods and potential descriptors. Twenty-nine sites were sampled along the coast of Provence and French Riviera (Southern France). Study sites were chosen with a view to encompassing a wide range of hydrological conditions and human pressures. Results Very well-preserved sites were found in Provence in areas without trawling and terrigenous inputs, while impacted and low-ES sites were located in the vicinity of urbanized areas. The cover of rhodoliths characterizes the seascape and might be an indicator of the good ES of CDB and reduced human pressure. However, the absence of rhodoliths may also be induced by natural phenomena. Discussion The EBQI designed for CDB proved representative and useful for a functional assessment based on epibenthic assemblages. However, some descriptors have shown their limitations and should be further explored. We highlight here the priority of establishing an index corresponding to a societal demand (e.g., European Directives, Barcelona convention) as a basis for a broad and large-scale assessment, for practical reasons. We stress the need to better apprehend the role of the macro-infauna and to extend this index over a wider geographical scale.